Manufactura y ensamble de una silla postural para niños de 1 a 3 años con parálisis cerebral (2020)
Cerebral palsy is a group of disorders in the development of movement, muscle tone and posture, this as a consequence of an aggression or abnormality on an immature brain. Paralysis not only affects the motor part of a person, but also cognitive, language, behavior, eating disorders occur, among others. In Colombia, according to the 2005 census, it was determined that 2% of children between 0 and 5 years old have some type of disability. And 70% of children with disabilities in Colombia live in poverty, which hinders their rehabilitation process. Therefore, with the help of Professor Luis Mario Mateus and with the support of the Aconiño Association, the manufacture and assembly of a postural chair was worked, based on the design made by the student Danna Salazar in her project entitled DESIGN OF A CHAIR POSTURAL FOR CHILDREN WITH CEREBRAL PARALYSIS . It should be clarified that posture chairs are part of the mechanical aids and that it is considered a sitting system that provides protection and stability to the user. In addition, it helps improve muscle tone, reduces musculoskeletal deformities and provides greater autonomy to the child to be able to carry out their daily activities.